I got a question recently, and have been unable to solve it.

If $1,\alpha_1,\alpha_2,\dots,\alpha_{n-1}$ are the roots of $X^n-1=0$, then find the value of $\prod{(1-\alpha_i)}$.

My solution:

The product will expand to $$1-\sum_{cyc}\alpha_i+\sum_{cyc}\alpha_i\alpha_{i+1}-\dots$$

This means I can use the relations of roots of a polynomial to its coefficients, thus getting this equal to

$1+0+0+\dots+0+0\pm1$, depending on whether $n$ is even or odd.

But the book gives the answer as $n$.

How does this happen? Please help.


The main flaw in your argument is that $\sum_{i=1}^{n-1} \alpha_i$ is not the sum of the roots of the polynomial: you are missing the root 1. Similarly $\sum_{i=1}^{n-1}\sum_{j=1}^{n-1}\alpha_i\alpha_j \neq 0.$

Here's a hint: given that the $\alpha_i$ are roots of $x^n-1$, can you write down a polynomial whose roots are $1-\alpha_i$?

  • $\begingroup$ Oh. I get it. I missed adding the $1$. Now, that's embarrassing. Thanks! $\endgroup$ Jul 28 '18 at 8:17

Notice that

$$\prod_{i=1}^{n-1} (X - \alpha_i) = \frac{X^n-1}{X-1} = X^{n-1} + X^{n-2} + \cdots + X + 1$$

so for $X = 1$ we get

$$\prod_{i=1}^{n-1} (1 - \alpha_i)= 1^{n-1} + 1^{n-2} + \cdots + 1 + 1 = n$$

Your approach can also be used but notice that $\alpha_1, \ldots, \alpha_{n-1}$ are roots of $X^{n-1} + X^{n-2} + \cdots + X + 1$, and not $X^{n}-1$ because the root $1$ is missing.


$$\prod_{i=1}^{n-1}(1-\alpha_i) = 1-\sum_{cyc}\alpha_i+\sum_{cyc}\alpha_i\alpha_{i+1}-\cdots = 1 - (-1) + 1 - \cdots = n$$

  • $\begingroup$ What do you mean by $X-\alpha_n$? Is it $\alpha_i$? And is this true for all $X,\alpha$? $\endgroup$ Jul 28 '18 at 8:19
  • $\begingroup$ @MalayTheDynamo Yes, $\alpha_i$ of course. $\endgroup$ Jul 28 '18 at 8:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.